Four views on the historical Adam. ([2013]) - Lamoureux, Denis O (Denis Oswald), 1954-; Walton, John H, 1952-; Collins, C. John, 1954-; Barrick, William D; Boyd, Gregory A, 1957-; Ryken, Philip Graham, 1966-
No abstract available